Sexual identity development: relationship with lifetime suicidal ideation in sexual minority women. Issue 23 (1st August 2016) - Dirkes, Jessica; Hughes, Tonda; Ramirez‐Valles, Jesus; Johnson, Tim; Bostwick, Wendy
Abstract : Aims and objectives: This study draws on a life course perspective to evaluate in a sample of sexual minority women: (1) the relationship between age at reaching sexual identity milestones and risk of suicidal ideation, (2) developmental stages or stages of sexual identity development that represent greatest risk and (3) the relationship between age of reaching milestones and parental support. Background: Research shows higher rates of suicidal ideation among sexual minority women than heterosexual women. Evidence suggests this is partly accounted for by risk factors including sexual identity development and parental support. However, it remains unclear whether there are stages of particularly high risk. Design: This is a cross‐sectional study. Data come from a prospective study of sexual minority women that used convenience and respondent‐driven sampling methods. Methods: Using logistic regression, we examined associations among age at sexual identity developmental milestones, parental support and suicidal ideation in a large ( N = 820), ethnically diverse sample of sexual minority women. Results: Compared with women who first wondered about their sexual identity in adulthood, those who first wondered in early, middle or late adolescence had greater odds of lifetime suicidal ideation. Younger age at subsequent milestones (first decided or first disclosed) was not associated with heightened risk of suicidal ideation. Parental support was independently associated with suicidal ideation. Conclusions: Findings suggest that where one is in the process of identifying as a sexual minority may be more important than age in understanding risk of suicidal ideation in this population. As individuals come to accept and integrate their sexual minority identity risks associated with younger age diminish. Relevance to Clinical Practice: Nurses and other healthcare providers who work with youth should routinely ask about sexual orientation and suicidal ideation and be aware that youth in the earliest stages of coming out as sexual minority may be at particularly high risk of suicide.